Vaccination timeliness in preterm infants - Sisson, Helen (2021)
Background Vaccination is a key public health activity, with established programmes primarily aimed at infants and children. Infants born prematurely are particularly vulnerable to infection, therefore the protection vaccination offers these infants is vital. Nonetheless, early reports specified that compared with their full term counterparts, preterm infants experience unwarranted delays in receiving vaccines. A contemporary review of the global literature indicated that the delay persists, however, the review also revealed a lack of research based on UK populations. Aim Taking a population-based approach, this study aimed to investigate the existence of a vaccination delay for preterm infants, and identify any factors associated with vaccination timeliness. Design and methods Using existing datasets, the study analysed data for infants born over a six-month period; this comprised of 4605 infants, and immunisation timeliness was studied for the primary series at eight, 12 and 16 weeks. Findings This study does not support the findings of previous research which has reported a negative correlation between gestational age and birthweight, and vaccination age. However, compared with their full term peers, infants classed as moderate to late preterm, or moderately low birthweight, experience greater delays for some vaccines at some of the series visits. The same delays were not observed in infants classed as very preterm, extremely preterm, or very low birthweight. None of the additional infant or parental characteristics studied influenced timeliness. Conclusion The moderate nature of infants’ prematurity and birthweight suggests that the delays observed in these infants more closely reflects immunisation practices in the community. It is important that all health professionals involved with families in the early weeks, regardless of care setting, promote and recommend vaccination. Parents should be offered individualised support with their decision making, which is provided by appropriately trained staff who are also knowledgeable of vaccine coverage in their area.
HydraID: hull:18472 Hydra Discover Access Group: public ETD Collection: ETDNursing
Keywords: Child health